2015
DOI: 10.1186/s13019-015-0320-z
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Gerbode defect following endocarditis of the tricuspid valve: a case report and literature review

Abstract: The Gerbode’s defect is a communication between the left ventricle and right atrium. It is usually congenital, but rarely is acquired, as a complication of endocarditis, myocardial infarction, trauma, or after previous cardiac surgery. The acquired Gerbode defect with involvement of the tricuspid valve acquired after bacterial endocarditis can be challenging to repair. We present a rare case of young woman, with endocarditis of the tricuspid valve and acquired Gerbode defect without previous cardiac surgery. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 25 publications
(36 reference statements)
0
40
0
21
Order By: Relevance
“…No data were available on IE in Albania, except a few cases reports of S. aureus [7] , [8] and Streptococcus bovis [9] endocarditis.…”
Section: Resultsmentioning
confidence: 99%
“…No data were available on IE in Albania, except a few cases reports of S. aureus [7] , [8] and Streptococcus bovis [9] endocarditis.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that LV-RA shunts in association with VSDs increases the risk of endocarditis (58 per 10,000 patient–years) in comparison to typical VSDs or mitral regurgitation (5.2 per 10,000 patient–years) [15], [32]. MI associated ANIGD has been reported with inferior wall MI with the LV-RA shunt located in the basal septum but not anterior wall MI [37], [39], [72], [73]. LV-RA shunt caused by MI has a mortality rate of 80% [9].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Such defects are believed to close by forming an aneurysmal pouch through incorporating adjacent TV tissue. This morphogenetic process has been termed aneurysmal transformation [24], [32], [37], [38].…”
Section: Embryology and Pathologic Anatomymentioning
confidence: 99%
See 2 more Smart Citations